A Review of Literature on Using Social Media to Learn English in A Relaxed and Convenient Manner - Nurjannah, Lydia; Afrianti, Mita; Nazly, Rafi; Safitri, Yuslia; Ihsan, Muhammad Taufik (ETDC: Indonesian Journal of Research and Educational Review, 2021)
We often hear the media as a means of communication, or more commonly referred to as "social media." However, the media can also be used as a learning tool. In this case, the media is needed in learning to increase the spirit of learning in students. Because in this day and age, many people are dependent on and like social media. So we also wrote this paper with the aim of knowing the extent to which social media can improve students' learning of English. We analyze articles related to this topic to develop social media ideas to improve students' English learning.